Объяснение:
https://tex.z-dn.net/?f=%28x-1%29%28x%5E2%2B4x%2B4%29%3D4%20%28x%2B2%29%20%5C%5C%28x-1%29%28x%2B2%29%5E2-4%28x%2B2%29%3D0%5C%5C%28x%2B2%29%28%28x-1%29%28x%2B2%29-4%29%3D0%5C%5Cx%2B2%3D0%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%28x-1%29%28x%2B2%29-4%3D0%5C%5Cx_1%3D-2%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20x%5E2%2Bx-6%3D0%5C%5C.%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20x_%7B2%2C3%7D%3D%5Cfrac%7B-1%5E%2B_-%5Csqrt%7B1%2B24%7D%7D%7B2%7D%3D%5Cfrac%7B-1%5E%2B_-5%7D%7B2%7D%5C%5C.%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20x_2%3D-3%5C%20%5C%20%5C%20%5C%20x_3%3D2%5C%5COTBET%3Ax_1%3D-2%5C%20x_2%3D-3%5C%20x_3%3D2
y= -(x+2)²(x+4)² = - ( (x+2)(x+4) )² = - ( x² +6x+8 )²; || (x+2)(x+4) ⇄ x² +6x+8 ||
y ' = -2(x² +6x+8) *(x² +6x+8 ) ' =-2(x² +6x+8) *(2x +6) = - 4(x+2)(x+4)(x +3) .
y ' = - 4(x+4)(x+3)(x+2)
y ' + - + -
(-4) (-3) (-2)
y ↑ ↓ (убыв.) ↑ (возр. ↓
ответ :x = -3 точка минимума .
* * * (знаки(условно) ↑ - функция возрастает , ↓ - функция убывает * * *